2004
DOI: 10.1128/aac.48.10.3743-3748.2004
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Bacitracin Resistance in Enterococcus faecalis Is Mediated by an ABC Transporter and a Novel Regulatory Protein, BcrR

Abstract: Bacitracin resistance (bacitracin MIC, >256 g ml ؊1 ) has been reported in Enterococcus faecalis, and in the present study we report on the genetic basis for this resistance. Mutagenesis was carried out with transposon Tn917 to select for E. faecalis mutants with decreased resistance to bacitracin. Two bacitracin-sensitive mutants (MICs, 32 g ml ؊1 ) were obtained and Tn917 insertions were mapped to genes designated bcrA and bcrB. The amino acid sequences of BcrA (ATP-binding domain) and BrcB (membrane-spannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 35 publications
4
119
2
1
Order By: Relevance
“…Interestingly, this TCS regulates not only a downstream operon encoding an ABC transporter (BceAB; MW2543-42), but also another operon encoding a transporter (VraDE; MW2620-2621), which is located separately from the TCS genes. In addition, transporters showing homology with BceAB have been reported in Gram-positive bacteria, including BcrAB from Bacillus licheniformis, 12 BcrAB from Enterococcus faecalis, 13 and MbrAB from Streptococcus mutans. 14 and as a survival strategy in the bacterial community.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Interestingly, this TCS regulates not only a downstream operon encoding an ABC transporter (BceAB; MW2543-42), but also another operon encoding a transporter (VraDE; MW2620-2621), which is located separately from the TCS genes. In addition, transporters showing homology with BceAB have been reported in Gram-positive bacteria, including BcrAB from Bacillus licheniformis, 12 BcrAB from Enterococcus faecalis, 13 and MbrAB from Streptococcus mutans. 14 and as a survival strategy in the bacterial community.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Because UPP acts as a carrier of peptidoglycan monomeric units across the cell membrane (2), the antibacterial nature of bacitracin results from its ability to block cell wall synthesis. High level bacitracin resistance in Enterococcus faecalis is encoded by the bcrABD operon that is under the control of a putative membrane-bound DNA-binding protein, BcrR (3). In the presence of bacitracin, transcription of the bcrABD operon leads to the production of BcrA and BcrB, which are proposed to act as an ABC exporter of bacitracin, thus conferring high level bacitracin resistance (minimum inhibitory concentration Ն 256 g/ml) to the cell (3).…”
mentioning
confidence: 99%
“…High level bacitracin resistance in Enterococcus faecalis is encoded by the bcrABD operon that is under the control of a putative membrane-bound DNA-binding protein, BcrR (3). In the presence of bacitracin, transcription of the bcrABD operon leads to the production of BcrA and BcrB, which are proposed to act as an ABC exporter of bacitracin, thus conferring high level bacitracin resistance (minimum inhibitory concentration Ն 256 g/ml) to the cell (3). BcrD is proposed to function as an undecaprenyl pyrophosphate phosphatase that functions to increase the amount of undecaprenyl available to the cell (3).…”
mentioning
confidence: 99%
“…TPPC shows potent activity against staphylococci, enterococci, streptococci, and bacilli, while enterococci, some streptococci, and bacilli show resistance to BAC, because of their BAC efflux systems (1,(16)(17)(18)(19). From our study using mutants with defects in the BAC efflux system, such as bceR, bceS, and ywoA (bcrC) mutants, it was revealed that TPPC is equally active against B. subtilis strain 168, despite the presence of these efflux systems (Table 4).…”
Section: Discussionmentioning
confidence: 84%